2019
DOI: 10.1002/clc.23145
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance influences the impact of hypertension on left ventricular diastolic dysfunction in a community sample

Abstract: Background Although obesity‐associated metabolic abnormalities (insulin resistance‐IR) may not play as marked a role in determining left ventricular (LV) diastolic dysfunction (DD) as hypertension, the impact of combinations of these risk factors on DD is unknown. Hypothesis We hypothesized that IR influences the impact of hypertension on DD. Methods In 704 randomly selected participants from a community sample with a high prevalence of hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The relationship between arterial blood pressure and IR has been shown in many studies 42,43 In our study, we found that systolic blood pressure is an independent predictor of IR. This may be due to increased fat tissue in the body that plays an important role in IR and subclinical inflammation caused by inflammatory cytokines, such as IL-6, IL-1 and TFN-alpha secreted from this adipose tissue.…”
Section: Discussionsupporting
confidence: 69%
“…The relationship between arterial blood pressure and IR has been shown in many studies 42,43 In our study, we found that systolic blood pressure is an independent predictor of IR. This may be due to increased fat tissue in the body that plays an important role in IR and subclinical inflammation caused by inflammatory cytokines, such as IL-6, IL-1 and TFN-alpha secreted from this adipose tissue.…”
Section: Discussionsupporting
confidence: 69%
“…The inter-rater agreement between manual assessments was less than moderate, and it was poor between automated and manual, which demonstrates substantial variability in how algorithms are applied by clinicians [56]. Moreover, the discussion of methodology in Bamaiyi et al illustrates how difficult it may be to observe guidelines fully, consistently, and accurately (e.g., keeping to the recommended number of diagnostic criteria throughout) [57].…”
Section: Left Ventricular Diastolic Dysfunctionmentioning
confidence: 99%
“…Of interest, even though HOMA-IR, an insulin resistance index, was not significantly associated with E/A in simple regression analysis, it was significantly and inversely associated with E/A after adjustment for other clinical factors, suggesting that insulin resistance may be a potential predictor of preclinical cardiac diastolic dysfunction. Limited numbers of population based studies suggest insulin resistance may enhance the impact of hypertension on preclinical cardiac diastolic dysfunction [ 35 , 36 ]. Our results clearly show importance of insulin resistance in the pathogenesis of LV diastolic dysfunction in patients with glycemic abnormalities.…”
Section: Discussionmentioning
confidence: 99%